Al-Istifâdah Min Adawât al-Syarṯ Ghayru al-Jâzimah Fî Sûrah Âli ‘Imrân Fî Ta’lîm al-Arabiyah Li al-Nâṯiqîn Bi Ghayrihâ - Agus Pujiartha, Lalu; Mahmudi, Muhlish; Firdaus, Rizal (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2025)
This study aims to identify the verses that include the Adawât al-Syart Ghayru al-Jâzimah in Surat Âli ‘Imrân, and to know the tool of the condition, its action and its answer in each of those verses, and to benefit from it in teaching Arabic to non-native speakers. The researcher carried out this study due to the importance of these tools, as they are common tools that have been repeated a lot in speech in general and in the Holy Qur'an in particular. To achieve the previous objectives, the researcher followed for this study the descriptive and analytical approach, by tracking the verses containing the Adawât al-Syart Ghayru al-Jâzimah in Surat Al-Imran, and collecting, analyzing, classifying, presenting and concluding from their study. After presenting the Adawât al-Syart Ghayru al-Jâzimah in Surat Al-Imran, the researcher presented how to benefit from Adawât al-Sharṯ Ghayru al-Jâzimah in Surat Âli 'Imrân in teaching Arabic to non-native speakers by providing guidance for teaching Adawât al-Syart Ghayru al-Jâzimah to students at the secondary level and providing exercises to know the extent of students' understanding, and this study proved that it is possible to benefit from Adawât al-Syart Ghayru al-Jâzimah in Surat Al-Imran in teaching Arabic to non-native speakers, and that it can facilitate the process of teaching Arabic and facilitate learning and understanding for Arabic learners.